RP-HPLC Method for Simultaneous Estimation of Bromohexine Hydrochloride, Dextromethorphan Hydrobromide and Guaiphenesin in Soft Gel Capsules - Mehta, P.S.; Patel, V.B. (Asian Journal of Chemistry, 2013)
A simple, precise and accurate reverse phase high performance liquid chromatographic method has been developed for simultaneous estimation of guaiphenesin, dextromethorphan hydrobromide and bromohexine hydrochloride in their soft gel formulations. The chromatographic conditions were standardized using Phenomenex Luna C18 (250 mm × 4.6 mm i.d., 5 μm particle size) with UV detection at 258 nm and mobile phase consisting of methanol: 0.05 M phosphate buffer pH 3.0 (60 : 40 v/v). Mobile phase was delivered at the flow rate of 1.3 mL/min and separation was completed within 8 min. The retention times of guaiphenesin, dextromethorphan hydrobromide and bromhexine hydrochloride were 3.1 min, 4.1 min and 6.8 min respectively. Calibration curves were linear with correlation coefficient 0.998. 0.999 and 0.999 over a concentration range of 50-250, 5-25 and 1-6 μg/mL for guaiphenesin, dextromethorphan hydrobromide and bromhexine hydrochloride respectively. Recoveries were between 97.04-100.15, 101.92-104.67 and 102.01-102.55 respectively. The proposed method was validated and successfully applied to the estimation of three drugs in combined soft gel formulation.